Prevalence of Thinness and Stunting and Associated Factors among Adolescent School Girls in Adwa Town, North Ethiopia. (16th May 2016) - Gebregyorgis, Tsgehana; Tadesse, Takele; Atenafu, Azeb
Abstract : Introduction . Despite the fact that adolescence is a window of opportunity to break the intergenerational cycle of malnutrition, adolescents are the neglected age groups. Hence information regarding the nutritional status of adolescents is lacking making creating and implementing intervention programs difficult. Objective . To assess the prevalence of thinness, stunting, and associated factors among adolescent school girls in Adwa town, Northern Ethiopia. Methods . Data on 814 adolescent female students were collected from March to April 2015 using interviewer administered pretested semistructured questionnaire and anthropometric measurements. Data were entered using EPI INFO version 3.5.3 and analyzed using SPSS version 20 and WHO Anthroplus software. Results . The prevalence of thinness and stunting was 21.4% and 12.2%, respectively. Age of adolescent [AOR = 2.15 (1.14, 4.03 )], mother's educational status [AOR = 2.34 (1.14, 4.80 )], eating less than 3 meals per day [AOR = 1.66 (1.12, 2.46 )], having family size >5 [AOR = 2.53 (1.66, 3.86 )] were significantly associated with thinness among the adolescent girls. Family size >5 [AOR = 2.05 (1.31, 3.23 )] and unimproved source of drinking water [AOR = 3.82 (2.20, 6.62 )] were significantly associated with stunting. Conclusion and Recommendation . Thinness and stunting are prevalent problems in the study area. Strategies to improve the nutritional status of girls should be given much attention.